Flapless submucosal instrumentation treatment of peri‐implantitis: Contemporary evidence and clinical protocol - José Nart; Neus Carrió; Gonzalo Blasi; Maria Costanza Soldini; Ramon Pons; Matteo Albertini; Beatriz de Tapia (Periodontology 2000, 2026)
Abstract Background/Aim Peri‐implantitis is a plaque‐associated disease characterized by inflammation of the peri‐implant mucosa and progressive loss of supporting bone, representing a growing clinical and public health challenge. Conventional nonsurgical therapies often provide limited and unpredictable outcomes, while surgical approaches are associated with increased morbidity and variable long‐term success. In this context, minimally invasive strategies, particularly flapless submucosal instrumentation, have emerged as a potential alternative or adjunct in the management of peri‐implantitis. The aim of this narrative review is to critically appraise the contemporary evidence on flapless treatment approaches for peri‐implantitis. Materials and Methods This narrative review analyzes the available literature on flapless submucosal instrumentation for peri‐implantitis, presented as a minimally invasive access approach performed without flap elevation that combines submarginal instrumentation with deliberate peri‐implant degranulation/curettage to improve access to the defect and implant surface, and may be considered in treatable, selected peri‐implantitis cases within a stepwise care pathway. The biological rationale for flapless therapy is discussed based on the histopathological characteristics of peri‐implant lesions, emphasizing the role of inflamed peri‐implant soft tissues as a persistent reservoir of infection. Current mechanical, chemical, and adjunctive modalities employed within flapless protocols are reviewed. Results Clinical, radiographic, systemic, and patient‐reported outcomes associated with flapless treatment approaches are examined. In addition, indications, limitations, and prognostic factors—including defect morphology, implant surface characteristics, prosthetic design, and patient‐related risk factors—are analyzed. Conclusion Although the available evidence remains heterogeneous and is largely derived from nonrandomized studies, flapless submucosal instrumentation appears to be a biologically sound and minimally invasive option for selected peri‐implantitis cases, which may be repeated when clinically indicated while acknowledging heterogeneous protocols and limited comparative evidence. Clinical Relevance Flapless submucosal instrumentation may reduce the need for more extensive surgical interventions. Practical clinical recommendations and step‐by‐step treatment algorithms are proposed to support evidence‐based and patient‐centered decision‐making in the management of peri‐implantitis.